Dental Caries in Young Children: Epidemiology, Etiology, Prevention, Treatment - Turayev Alimjan Baxriddinovich (Scientific Trends, 2024)
Dental caries in children is a special disease that has a complex multifactorial nature of multifaceted interactions. The assessment of the strength and degree of influence of risk factors for the development of this disease should be carried out in the specific conditions of the patient, taking into account the stage of development and age-related structural features of the baby's teeth, as well as exogenous and endogenous conditions. Since some of the risk factors for caries are associated with more or less objective conditions, attempts by the "patient" or dentist to influence them are limited and can only be partially changed. However, a large group consists of risk factors that depend on the behavior of the child and his parents and can be minimized by both the dentist and self-help efforts. In this case, these factors are the main objects determining the scope and focus of therapeutic and preventive measures.
Keywords: Baby teeth, childhood caries, risk factors, therapeutic and preventive measures.